Strategi Akumulasi Modal Pembelajar Muda Bahasa Jepang di Ranah Digital - Wury Dwiwardani; Oki Rahadianto Sutopo; Wiwik Sushartami (Jurnal Studi Pemuda, 2025)
This article discusses strategies employed by young Japanese-language learners to accumulate cultural capital related to Japanese language proficiency within a field that is undergoing significant transformation due to the development of internet technology. These technological developments have reshaped the field by enabling autonomous accumulation of Japanese-language cultural capital, expanding opportunities for flexible learning, and opening up spaces for personalized learning. Based on a qualitative study of four informants, this article identifies three main patterns of youth strategies for navigating online learning activities. These strategies are shaped by reflexivity, which interacts with their habitus, digital capital, and previously accumulated forms of capital. These strategies are referred to in this article as systematic exploration, selective-limited exploration, and affective exploration. Through these strategies, the youth, who are agents in the field of Japanese language learning, mobilize their habitus, digital capital, and other previously accumulated capital to respond to, adapt to, and negotiate within the dynamics of a field increasingly structured by digital technologies.